CHEMICAL EVOLUTION OF THE PERMIAN-TRIASSIC BASALTS OF THE SIBERIAN PLATFORM IN SPACE AND TIME - Al'mukhamedov A.I.; Medvedev A.Ya.; Zolotukhin V.V. (My University, 2004)
Using a database on the geochemical stratigraphy of the Permian-Triassic lava sequence of the Siberian platform, we analyzed the space-time distribution of various basalt types. Two adjacent stages of magmatic activity were distinguished. The products of the first stage (cycles 1-3) are represented by a strongly differentiated series of basalts varying in both silica and alkali contents. They occur only in the northwest and north of the Tunguska syneclise, in the flanks of paleorift structures, where they are confined to the lower parts of stratigraphic sections of the lava sequence. This stage of magmatic activity is correlated with rift-forming events. The second-stage volcanics (cycles 4 and 5) are low-potassium tholeiitic basalts of an undifferentiated series occurring over the whole area of the basaltic plateau. In the case of their cooccurrence with rift-related basalts, the low-potassium tholeiitic basalts are statistically confined to the middle and lower parts of stratigraphic columns. This phase is referred to as the off-rift or flood basalt proper stage. The products of the sixth magmatic cycle, mainly alkaline volcanics, occur only in the Maimecha-Kotui province of the northeastern Siberian platform and are not considered in detail in this paper. A schematic plume tectonic model is proposed for the volcanism of the Siberian platform. It is supposed that the considerable thickness of cold lithosphere beneath ancient platforms and the existence of consolidated mature crust hindered rapid transport of basaltic magmas from their sources toward the surface. This resulted in the accumulation and differentiation of melts in the plume head arrested at the boundary of the lithospheric mantle. An increase in extensional stresses during further plume ascent and predominance of brittle deformations in the strongly metamorphosed Precambrian crust have eventually led to geologically instantaneous eruption of residual tholeiitic melts accumulated in transitional magma chambers. The extensive eruptions of melts were probably triggered by an abrupt change in the kinematics of the Eurasian plate at the Permian-Triassic boundary.
Keywords: Siberian platform; basalt; Mesozoic::Triassic; Paleozoic::Permian; Мезозой::Триасовая; Палеозой::Пермская